Evaluating the viability of installing photovoltaic panels on irrigation canals for energy generation and water storage - Ali Kaab; Hassan Ghasemi-Mobtaker; Mohammad Sharifi; Uffe Jørgensen (Energy Nexus)
This innovative strategy leverages solar energy to deliver clean, renewable power for irrigation pumps and related equipment, while also facilitating water storage. A study conducted by the IKAIC in Khuzestan province, Iran, explored the installation of PV systems on canal irrigation systems. The study indicates a PV system generates 7.22 GJ of solar energy per m² annually. To power the study area, about 23.3 ha of panels are needed. Utilizing the 114 ha of irrigation canals, if fully covered, could yield around 8233 TJ of energy, with an excess of 6550 TJ available for the grid. However, mutual shading limits usable panel coverage to 60 %, resulting in about 68.40 ha of coverage and generating approximately 4940 TJ, with 3257 TJ connectable to the grid. The analysis revealed that initial evaporation from the canal surface was around 1389,597 m³ annually. After the installation of PV panels, this figure fell to 764,278 m³, reflecting a reduction of 625,319 m³. This transforms to an approximate decrease of 11 ± 4 thousand m³ of water evaporation per km of canal. Thus, the implementation of PV panels on irrigation canals is highly recommended for both energy production and water conservation. This approach optimizes land use, supports sustainable development, and tackles the intertwined challenges of energy generation and water management. By harnessing solar power and utilizing existing infrastructure, this solution offers the potential to transform energy production and water resource management.